The Influence of Sharia Financial Literacy, Gold Price Fluctuations, Risk Perception and Culture on Customer Decisions to Choose Gold Installments at Bank Syariah Indonesia KC Padangsidimpuan - Miftahul Janna Ritonga; Leny Nofianti; Hariza Hasyim (LP2M IAIN Palopo, 2026)
This study aims to analyze the influence of Islamic financial literacy, gold price fluctuations, risk perception, and culture on customers’ decisions to choose gold installment products at Bank Syariah Indonesia KC Padangsidimpuan. The study was motivated by the increasing use of gold installment products despite fluctuations in gold prices, as well as the strong cultural values that influence gold ownership within the community. This research employed a quantitative approach with a sample of 213 customers selected through purposive sampling from a population of 475 gold installment customers in 2025. Data were collected using questionnaires and analyzed through multiple linear regression with the assistance of SPSS Statistics 25. The results indicate that Islamic financial literacy, risk perception, and culture have a positive and significant effect on customers’ decisions, while gold price fluctuations have a positive but insignificant effect. Simultaneously, all independent variables significantly influence customers’ decisions to choose gold installment products. These findings suggest that customers’ decisions are influenced not only by economic and financial considerations but also by risk perceptions and cultural values embedded in society.